Rationale for surrogate endpoints and conditional marketing authorization of new therapies for kidney transplantation - Naesens, M; Loupy, A; Hilbrands. L; Oberbauer, R; Bellini, MI; Glotz, D; Grinyó, J; Heemann, U; Jochmans, I; Pengel, L; Reinders, M; Schneeberger, S; et al. (Wiley, 2022)
Conditional marketing authorization (CMA) facilitates timely access to new drugs for illnesses with unmet clinical needs, such as late graft failure after kidney transplantation. Late graft failure remains a serious, burdensome, and life-threatening condition for recipients. This article has been developed from content prepared by members of a working group within the European Society for Organ Transplantation (ESOT) for a Broad Scientific Advice request, submitted by ESOT to the European Medicines Agency (EMA), and reviewed by the EMA in 2020. The article presents the rationale for using surrogate endpoints in clinical trials aiming at improving late graft failure rates, to enable novel kidney transplantation therapies to be considered for CMA and improve access to medicines. The paper also provides background data to illustrate the relationship between primary and surrogate endpoints. Developing surrogate endpoints and a CMA strategy could be particularly beneficial for studies where the use of primary endpoints would yield insufficient statistical power or insufficient indication of long-term benefit following transplantation.